2016
DOI: 10.1111/eea.12494
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of host resources influence foraging strategy in parasitoids

Abstract: International audienceMany species have to cope with decreased resource availability and life expectancy during winter. The optimal foraging theory predicts that under these conditions, generalist foraging strategies should be favoured, via the acceptance of suboptimal resources. In contrast, during favourable seasons, specialist foraging strategies, i.e., a preferential consumption of the most profitable resources, should be favoured instead. Although spatial and fine-scale temporal dimensions of the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Indeed, female parasitoids show seasonal variations in foraging behavior (Roitberg et al, 1992) and can adapt their foraging strategies to competition or host-patch quality (Barrette et al, 2010;Le Lann et al, 2008;Moiroux et al, 2015;Outreman et al, 2005). In winter, it has been demonstrated that female parasitoids adopt generalist strategies due to shortage of optimal hosts, leading to high competition, whereas spring parasitoids usually display specialist strategies by selecting optimal host species (Eoche-Bosy et al, 2016). The recent addition of A. avenae and A. ervi in the overwintering food web, which are good competitors at exploiting S. avenae, may have reduced the abundance of A. matricariae and A. rhopalosiphi Eoche-Bosy et al, 2016;Le Lann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, female parasitoids show seasonal variations in foraging behavior (Roitberg et al, 1992) and can adapt their foraging strategies to competition or host-patch quality (Barrette et al, 2010;Le Lann et al, 2008;Moiroux et al, 2015;Outreman et al, 2005). In winter, it has been demonstrated that female parasitoids adopt generalist strategies due to shortage of optimal hosts, leading to high competition, whereas spring parasitoids usually display specialist strategies by selecting optimal host species (Eoche-Bosy et al, 2016). The recent addition of A. avenae and A. ervi in the overwintering food web, which are good competitors at exploiting S. avenae, may have reduced the abundance of A. matricariae and A. rhopalosiphi Eoche-Bosy et al, 2016;Le Lann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Data consist in aphid-parasitoid pairs of species gathered from different studies conducted in the Long Term Ecological Research (LTER) ZA Armorique, France (48.29 °N -1.35 °W), each winter from 2009/10 to 2017/18, at variable dates from late-November to mid-March of each year (excepted in 2009/10 when sampling was conducted only in January and February). Data from winter 2009/10 to winter 2012/13 were obtained from Andrade et al, (2016) and Eoche-Bosy et al, (2016), data of 2013/14 from Tougeron et al, (2016), data of 2014/15 from Tougeron et al, (2017), data of 2015/16 from Damien et al, (2017) and data of 2016/17 and 2017/18 from unpublished field results. In winter 2010/2011, no parasitoids nor aphids were found in the fields due to frost conditions during 15 consecutive days in November so this winter was excluded from the dataset to minimize unbalanced analyses on community data.…”
Section: Data Collectionmentioning
confidence: 99%
“…The phenotypic space packing would then depend on the host selection behavioural strategies in each species of the guild. Some studies conducted on the selection of host species by aphid parasitoids have suggested some host preferences (Andrade et al., ; Eoche‐Bosy, Outreman, Andrade, Krespi, & van Baaren, ). So, the hypervolumes estimated here depended on the host species used by the parasitoids collected and this behavioural effect on niche differentiation must be included in the set of features driving phenotypic evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, host species influenced parasitoid longevity but not their body size, forewing area nor sex allocation. In relation to longevity, it is possible that the energy reserve accumulated and/or the energy consumption rate would differ between parasitoids emerging from the Some studies conducted on the selection of host species by aphid parasitoids have suggested some host preferences (Andrade et al, 2013;Eoche-Bosy, Outreman, Andrade, Krespi, & van Baaren, 2016).…”
Section: Life-history Traits In Food Websmentioning
confidence: 99%
“…dirhodum [24]. Furthermore, aphid hosts are known to impact the morphology and some life history traits of the emerging parasitoid [28, 29]. As such, an effect of host species cannot be ruled out and may impact the intensity and / or the form of host manipulation observed, particularly if host species differ in their inherent thermal tolerance.…”
Section: Introductionmentioning
confidence: 99%